PELAKSANAAN PEMBELAJARAN DARING DI SD NEGERI 3 DESA MUARA BURNAI - Monika Ika Widiarti (Jurnal PGSD Musi, 2020)
The background of this research is that online learning programs that have been set by the government are not well followed by students. This research entitled “Implementation of Online Learning in SD Negeri 3 Muara Burnai 1 village”. This study aims to describe the implementation of online learning in SD Negeri 3 Muara Burnai 1 village. This research uses qualitative research methods, which prioritizes the process of occurrence of events in natural situations. Research subject in this study are 3 students who can fill out a questionnaire that has been distributed and the homeroom teacher. Data colletion techniques in this study by giving questionnaris to students and interviews. Data analysis techniques used in this study is by conducting interviews with respondents. The results of this study are the implementation of online learning in SD Negeri 3 Muara Burnai 1 village has not been implemented well. This can be seen form the online learning process that is not followed by students from the beginning to the end of learning.